A perspective from key stakeholders on football and health improvement. (3rd March 2016) - Martin, Angus; Morgan, Simon; Parnell, Daniel; Philpott, Matthew; Pringle, Andy; Rigby, Michael; Taylor, Andy; Topham, Jon
Abstract : Football is one of the most popular sports worldwide. Much of the research literature is primarily focused on contributions from the academic community. Given this, the Editors were motivated to provide an opportunity for practitioners and commissioners from applied settings to share their perspectives. This applied article offers insights from 'key players' activity involved in football-led health improvement interventions.